(untitled) (UNIZIK Journal of Educational Management and Policy, 2026)
This study examined the institutional challenges and lecturers’ level of job satisfaction in public universities in Anambra State. Four research questions guided the study. A descriptive survey research design was employed in the study. Population for the study comprised 3,247 lecturers from two public universities in Anambra State. Sample size of the study constituted 1,624 lecturers from the total population selected using proportionate stratified random sampling technique. A researcher-developed 36-item questionnaire titled: “Institutional Challenges and Level of Lecturers Job Satisfaction Questionnaire (ICLLJSQ)” and structured on a 4-point rating scale, served as instrument for data collection. Both validity and reliability of questionnaire was established. Data collated were analyzed using mean statistics rated at 2.50 and standard deviation statistics. Findings indicated a generally low level of lecturers’ job satisfaction arising from all the identified institutional challenges as regards to the working conditions, research and academic support, administrative leadership, and remuneration challenges. The study recommended among others that the University managements in collaboration with government (both federal and state) and relevant stakeholders, should prioritize the improvement of lecturers’ working conditions to curb certain relative challenges through the provision and maintenance of adequate office spaces, modern teaching facilities, functional laboratories, reliable internet services, and stable power supply, in order to increase lecturers’ high level of job satisfaction.